Mechanism of antibody-specific deglycosylation and immune evasion by Streptococcal IgG-specific endoglycosidases - Beatriz Trastoy; Jonathan J. Du; Javier O. Cifuente; Lorena Rudolph; Mikel García-Alija; Erik H. Klontz; Daniel Deredge; Nazneen Sultana; Chau G. Huynh; Maria W. Flowers; Chao Li; Diego E. Sastre; et al. (Nature Communications, 2023)
Bacterial pathogens have evolved intricate mechanisms to evade the human immune system, including the production of immunomodulatory enzymes. Here, the authors establish the mechanisms of recognition and specific deglycosylation of IgG antibodies by the multi-modular enzymes EndoS and EndoS2